Chronic persistent HHV‐6B infection after sulfasalazine‐induced DRESS with demonstration of HHV‐6 encoded small noncoding RNAs (sncRNAs) in Crohn's‐like colitis: Case report. Issue 2 (18th December 2020) - Descamps, Vincent; Gautheret‐Dejean, Agnès; Pelletier, Anne‐Laure; Bonnafous, Pascale; Deschamps, Lydia; Prusty, Bhupesh K.
Abstract: A sulfasalazine‐induced DRESS (Drug Reactivation with Eosinophilia and Systemic Symptoms) was complicated by a Crohn's‐like colitis. We demonstrated HHV‐6 reactivation with presence of HHV‐6 DNA and small noncoding RNA in colonic lesions. This observation confirms the major role of HHV‐6 reactivation in DRESS manifestations and the importance of looking for HHV‐6 reactivation in DRESS. Abstract : A sulfasalazine‐induced DRESS (Drug Reactivation with Eosinophilia and Systemic Symptoms) was complicated by a Crohn's‐like colitis. We demonstrated HHV‐6 reactivation with presence of HHV‐6 DNA and small noncoding RNA in colonic lesions. This observation confirms the major role of HHV‐6 reactivation in DRESS manifestations and the importance of looking for HHV‐6 reactivation in DRESS.